(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Udavarta, an Ayurvedic condition caused by the reversal of Apana Vata, results from factors like Vegadharana (suppression of natural urges), excessive intake of Ruksha (dryness), Kashaya (astringent), Tikta (bitter), Katu (pungent) foods, Upavasa (fasting), and Ativyavaya (indulging in excessive sexual acts). This leads to disturbances in the downward movement of stool, urine, and Vata, causing symptoms such as Vibandh (constipation), Adhmana (abdominal distension), Hrillasa (nausea), Shoola (pain), and Avipaka (indigestion). If left untreated, Udavarta can contribute to systemic complications affecting the respiratory, digestive, cardiac, urinary, and nervous systems, even bleeding disorders. Modern diseases such as irritable bowel syndrome (IBS) and chronic constipation show similarities with Udavarta. A meta-analysis by Barberio et al. reported a prevalence of functional constipation ranging from 10.1% to 15.3%, highlighting the need for effective dietary interventions. Although current guidelines lack specificity regarding food choices. So, this review article was done to prepare an Ayurvedic dietary chart form Ayurvedic classics that can play an important role in prevention as well as management of Udavarta. Ahara Draya having Snigdha (unctuousness), Mridu (softness), Saraka (purgative), Vatanulomaka (proper elimination of flatus), Varchobhedi (causing diarrhea/loose motions), Srushtamutrapurisha (easy elimination of stool, urine), Vibandhghna (anti-constipative), Udavartahara properties. These Dravya treat Udavarta by softening the stool, clearing Purishavaha Srtotas, easy passage of stool, elimination of flatus, and pacify Vata. Pathya Ahara should be included in diet along with medication for the better management of Udavarta after proper assessment of Agni Bala (digestive power), Koshta (alimentary canal), Prakriti (somatic constitution).